Globalisasi dan Transformasi Ekonomi Syariah: Tantangan dan Peluang di Era Disrupsi - Ja'far Nasution; Iskandar (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study examines the influence of globalization on the transformation of Islamic economics in the era of digital disruption. Globalization, characterized by the integration of international trade, cross-border investment, and the rapid development of digital technology, has significantly transformed the global economic system. Amid these dynamics, Islamic economics has emerged as an alternative economic system that emphasizes justice, transparency, sustainability, and social balance. This research aims to analyze the process of economic globalization, its impact on international trade, cross-border investment, global financial markets, and its implications for the development of Islamic economics. In addition, this study explores the challenges and opportunities of Islamic economics in the era of disruption and proposes a maqashid sharia-based framework for Islamic economic development. The research employs a qualitative approach using descriptive-analytical methods through library research. Data were collected from scientific journals, academic books, reports from international institutions, and various documents related to global and Islamic economics. The findings indicate that globalization provides significant opportunities for the growth of the halal industry, Islamic fintech, sharia investment, and digital-based Islamic economic systems. However, globalization also presents challenges such as the dominance of the global capitalist system, financial market volatility, complex technological developments, and low levels of Islamic economic literacy. This study concludes that the integration of maqashid sharia, digital transformation, state regulation, and technological innovation can strengthen the position of Islamic economics as an inclusive, just, and sustainable economic system amid the dynamics of globalization.